Mini review: Intensification of mulching to improve soil moisture in vanilla plantation - I Gede Ketut Adiputra (Universitas Gadjah Mada, 2018)
Continuous water uptake from soil via the root system and it transport into the leaves system is a basic mechanism in plants to maintain growth and reproduction. Consequently, sustaining soil moisture to keep water supply into the plants should continuously occurred to maintain growth. Under condition of global warming scenario and robust agricultural practices, soil organic carbon which plays as a key for soil moisture and fertility are continuously diminished. This condition could subsequently endanger the growth of shallow rooted plants, such as vanilla. To mitigate the impact of global warming and robust agricultural practices, enhancing carbon sequestration to inhibit water loss is regarded crucial. However, although mulch materials are locally available in most land crop plantations, those materials are rarely viewed as functional for maintaining soil moisture. Both water stress and mulching might have not been seriously anticipated in conventional agricultural practices. For example, continuous decreased in yield of vanilla plants are usually handled by applying pesticide or fertilizer, without addition of mulch. The objective of this review was to gain a better understanding of soil moisture to increase vanilla growth and reproduction. This review found that mulching could reduce evaporation, increase soil organic carbon and soil fertility. It is concluded that intensification of mulching could enhance sustainability of vanilla plantations.